2006
DOI: 10.4143/crt.2006.38.3.144
|View full text |Cite
|
Sign up to set email alerts
|

AKAP12α is AssoCiated with Promoter Methylation in Lung Cancer

Abstract: P urpose: P romoter methylation is an important mechanism for silencing tumor-suppressor genes in cancer and it is a promising tool for the development of molecular biomarkers. The purpose of the present study was to investigate whether inactivation of the A Kinase Anchoring P rotein 12 (AKAP 12) gene is associated with promoter methylation in lung cancer.M aterials and M ethods: The AKAP 12 expression was examined by reverse transcription-polymerase chain reaction (R T-P C R ) in ten lung cancer cell lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…This is consistent with other studies showing that AKAP12 expression is associated with epigenetic modifications such as promoter hypermethylation [27][28][29][30]. However, the removal of HDAC7 is only a prerequisite for the transcriptional machinery to induce the gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other studies showing that AKAP12 expression is associated with epigenetic modifications such as promoter hypermethylation [27][28][29][30]. However, the removal of HDAC7 is only a prerequisite for the transcriptional machinery to induce the gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…In silico analyses at the Cancer Genome Anatomy Project SAGE (Serial Analysis of Gene Expression) site (http://cgap.nci.nih.gov/SAGE) identify AKAP12 downregulation in human thyroid, lung and liver cancer tissue, in human ovarian cancer cell lines. The majority of cancers suffering from epigenetic AKAP12 silencing seem to be regulated via promoter hypermethylation (70, 78, 85, 88, 99, 100), although instances exist where AKAP12 silencing is through changes in histone acetylation (78). Indeed, the silencing of AKAP12 via promoter hypermethylation (101, 102) has been shown to function as a neoplastic progression biomarker in Barrett’s esophagus (103).…”
Section: Introductionmentioning
confidence: 99%
“…AKAP12 (aka SSeCKS and Gravin) has demonstrable growth suppressive properties and is down-regulated in a variety of human neoplasms supporting the idea that AKAP12 is a bonafide tumor suppressor gene [32], [34], [36][40]. However, there is little information on the role of AKAP12 in non-neoplastic cell growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies demonstrated the importance of serum response factor-binding CArG boxes in the regulation of Akap12α promoter activity [48]. Adjacent GC-rich sequences in the Akap12α promoter were shown to undergo hypermethylation and gene silencing in various cancer cell lines; in contrast, the Akap12β promoter exhibited less gene silencing in cancer cells [34], [39], [40]. A subsequent study demonstrated a methylation-independent mechanism for Akap12α promoter silencing through the recruitment of HDAC1 [49].…”
Section: Discussionmentioning
confidence: 99%